Marine Anthropogenic Litter 2015
DOI: 10.1007/978-3-319-16510-3_5
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Mixture, Fate and Toxicity of Chemicals Associated with Plastic Debris in the Marine Environment

Abstract: For decades we have learned about the physical hazards associated with plastic debris in the marine environment, but recently we are beginning to realize the chemical hazards. Assessing hazards associated with plastic in aquatic habitats is not simple, and requires knowledge regarding organisms that may be exposed, the exposure concentrations, the types of polymers comprising the debris, the length of time the debris was present in the aquatic environment (affecting the size, shape and fouling) and the locatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
203
2
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(211 citation statements)
references
References 120 publications
(256 reference statements)
0
203
2
6
Order By: Relevance
“…Rochman et al (2016) conducted a critical and systematic review of published literature on the perceived, tested, and demonstrated impacts of anthropogenic debris (all materials in all environments) as a function of debris size and affected level of biological organization (i.e., assemblage, population, organism, and suborganism levels; note that the construct did not account for some behavioral or physiological responses, such as altered feeding, movement, or growth). A comprehensive review of the literature on encounters with and biological impacts of plastic marine debris is beyond the scope of this article, and I refer readers to several recent reviews for more detail (Gall & Thompson 2015, Kiessling et al 2015, Kühn et al 2015, Lusher 2015, Rochman 2015, Rochman et al 2016). Here, I present an overview of the types of encounters documented between marine organisms and plastic debris and the potential and demonstrated impacts of such encounters to convey the state of understanding, including major gaps that require further research.…”
Section: Wwwannualreviewsorg • Plastics In the Marine Environment 215mentioning
confidence: 99%
See 3 more Smart Citations
“…Rochman et al (2016) conducted a critical and systematic review of published literature on the perceived, tested, and demonstrated impacts of anthropogenic debris (all materials in all environments) as a function of debris size and affected level of biological organization (i.e., assemblage, population, organism, and suborganism levels; note that the construct did not account for some behavioral or physiological responses, such as altered feeding, movement, or growth). A comprehensive review of the literature on encounters with and biological impacts of plastic marine debris is beyond the scope of this article, and I refer readers to several recent reviews for more detail (Gall & Thompson 2015, Kiessling et al 2015, Kühn et al 2015, Lusher 2015, Rochman 2015, Rochman et al 2016). Here, I present an overview of the types of encounters documented between marine organisms and plastic debris and the potential and demonstrated impacts of such encounters to convey the state of understanding, including major gaps that require further research.…”
Section: Wwwannualreviewsorg • Plastics In the Marine Environment 215mentioning
confidence: 99%
“…Many of these substances are known to be persistent, bioaccumulative, and toxic (PBT), with at least 78% of the priority pollutants identified by the US EPA known to be associated with plastic marine debris (Rochman et al 2013a). PBT substances are typically hydrophobic and therefore readily sorb out of seawater onto other hydrophobic substances, such as sediment, organic matter, and now plastic (Rochman 2015). In fact, because of their strong attraction to PBT substances, some plastics are utilized as passive sampling devices to measure chemical contaminants in a variety of environmental matrices (Lohmann 2012).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…through ingested plastics or contamination with persistent organic pollutants, POPs). The body of literature describing the contamination of commercially exploited fish and shellfish by microplastic ingestion is growing rapidly, as is the literature analysing the consequences of this contamination on the health of individuals and populations (Galloway 2015;Lusher 2015;Rochman 2015). However, as yet there have been no economic assessments to estimate the costs of these impacts.…”
Section: Fisheriesmentioning
confidence: 99%